O efeito do fogo na remoção de sementes no Cerrado - Alcolea, Mirela (Universidade Federal de São Carlos, 2020)
Fire may modulates the dynamics, diversity and structure of many terrestrial ecosystems. Although the effects of fire are well studied for some plant and animal communities, the effects of fire on important ecological interactions, such as seed removal, are poorly known. In this study, we investigated the effect of fire on seed removal in a Cerrado. Through field experiments in sites burned one month or one year before, and in unburned control sites, we assessed the removal of different plant diaspores (sunflower seed, fruit of Miconia rubiginosa and artificial seed); agents of removal; and the influence of microhabitat features on seed removal. Treatments one-month post-fire had higher removal of sunflower seeds and M. rubiginosa fruit. Removal of artificial seeds did not differ among treatments. Ants were the main removers. The composition of ant species that remove diaspores varied with fire, but the relative frequency of different functional groups (based on diet, habitat and body size) were not affected by fire. Removal distance by the ants ranged from 4 to 390 cm, and was not affected by fire. Microhabitat features did not influence removal of diaspores. Overall, our results show that fire does not significantly change seed removal in the cerrado. A desirable next step is to investigate the impact of different fire regimes, such as different fire frequencies and extensions of the burned area, which could alter the effects on seed removal.
Fire effect on seed removal in the Cerrado
Keywords: Dispersão de sementes; Formigas; Interação planta-animal; Predação de sementes; Savana; Animal-plant interactions; Ant; Savanna; Seed dispersal; Seed predation; CIENCIAS BIOLOGICAS::ECOLOGIA